PENGGUNAAN MEDIA KARTU KATA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK DI TK BAITUL AZIIZ SURABAYA - Prapmawati Prapmawati; Wali Atiningsih (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
This study examines how to improve children's early reading skills through the method of playing word cards at Baitul Aziiz Kindergarten Surabaya. The approach used in this research is a qualitative approach, with the type of research being Classroom Action Research. From the results of student observations with indicators, the child's ability to distinguish the sound of words from the 15 students present, 4 children in the developing category as expected, and 1 student in the very well developed category. In the indicator of the child's ability to mention letter symbols according to sound, 3 children developed according to expectations (BSH), and 3 children developed very well. At the second meeting of cycle II there was an increase. From the results of student observations with indicators, the child's ability to distinguish the sound of words from the 15 students present was 2 children in the developing category as expected and 13 children in the very well developed category. In the indicator of the child's ability to mention letter symbols according to sound, 3 children developed according to expectations, and 12 children developed very well.